A afetividade no processo educativo segundo Henri Wallon: a influência da afetividade no processo educativo segundo Henri Wallon - Buuron, Beatriz da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The present work aims to address the issue of affectivity influence in the teaching- learning process. For this, we carried out a qualitative-bibliographic research, presenting analyzes of studies already carried out and published by Henri Wallon, a physician and psychologist who dedicated his career to education, believing in the reciprocal relationship that must exist between psychology and pedagogy. The author reports in his theory the five stages of child development and the role of affectivity in each of them and makes it clear how essential it is to establish an affective relationship between those involved in the school educational process, providing us with theoretical support to strengthen the idea that affectivity needs to be one of the axes of the school educational process. This evidence leads us to think about the professional training of teachers, as affectivity is still little explored and needs to be addressed according to its significance, becoming part of the teacher professional constitution.

O presente trabalho tem como objetivo abordar sobre o tema da afetividade no processo de ensino aprendizagem. Para isso, realizamos uma pesquisa bibliográfica, apresentando análises de estudos já realizados e publicados por Henri Wallon, médico e psicólogo que dedicou sua carreira à educação, por acreditar na relação recíproca que deve existir entre a psicologia e a pedagogia. O autor relata em sua teoria os cinco estágios de desenvolvimento infantil e o papel da afetividade em cada um deles e deixa evidente o quão essencial é o estabelecimento de uma relação afetiva entre os envolvidos no processo educativo escolar, nos fornecendo respaldo teórico para fortalecer a ideia de que a afetividade precisa ser um dos eixos do processo educativo escolar. Essa evidência nos leva a pensar na formação profissional dos professores, pois o tema da afetividade ainda é pouco trabalhado e precisa ser abordado de acordo com a sua significância, passando a fazer parte da formação profissional do docente.
Affectivity in the educational process according to Henri Wallon: the influence of affectivity in the educational process according to Henri Wallon
Keywords: Affection; Teaching-learning process; Child development; Psychogenetic theory; Afetividade; Processo ensino-aprendizagem; Desenvolvimento infantil; Teoria psicogenética